FACTORS OF FORMATION OF THE VALUE SYSTEM OF AN ADULT PERSONALITY - Яригіна, Олена (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2025)
Modern living conditions in Ukraine and the world require a high level of adaptation skills. One of the important tasks in such circumstances is the formation of reliable psychological supports, one of which may be the value system of the personality. This article presents a study of the factors that influence the formation and development of the value system of the personality. The aim of the study is to identify and analyze the factors of the development of the value system and their interconnections, as well as to determine the dynamics of the formation of value and moral orientations at different stages of personality development and to clarify their role in self-identification and the ability to make choices in changing life circumstances. The study used interdisciplinary theoretical and analytical approaches that included research into psychological, pedagogical, and cultural aspects of personality development. Methods of logical-structural analysis of existing scientific data were applied, as well as systematization, comparison, and structuring of the identified influencing factors on the formation of the personality’s value orientations. As a result of the study, the following influencing factors were identified: family upbringing, the experience of interpersonal interaction with other individuals in general and with significant adults or authoritative figures in particular, personal life experience, the level of need satisfaction, understanding the meaningfulness of social demands, the influence of the cultural and informational environment, and the level of personal subjectivity. Looking in more detail, the dynamic and variable nature of the formation of the value system can be noted. Thus, in early childhood, the dominant influence is exerted by emotionally safe relationships in the family, which affect the personality's ability to successfully integrate the proposed societal norms. In school age, the role of interpersonal interaction and learning moral norms within the collective comes to the forefront. The adolescent period is characterized by the actualization of the choice of a reference group and its influence on the individual. At this stage, a significant rethinking of previously formed value orientations may occur. At the stage of professional formation, critical thinking and the degree of integration between social and individual norms play an important role; various value and behavioral models are explored, and personal choice and moral regulation are implemented. Later, the mature personality forms a stable yet flexible value system that reconciles personal choices with the socio-cultural context. In conclusion, one can come to understand the value system as a dynamic structure that can constantly change under the influence of external and internal factors, while maintaining its supportive function and serving as an important element of self-awareness and personality adaptation to changing life conditions.